2020
DOI: 10.1097/mph.0000000000002029
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Pyomyositis in a Child With Acute Lymphoblastic Leukemia: A Case Report and Review of Literature

Abstract: Background: We report the case of an 11-year-old girl with a recent diagnosis of common B-cell acute lymphoblastic leukemia who presented with Pseudomonas aeruginosa pyomyositis of the left lower limb during severe neutropenia associated with the induction phase of chemotherapy. Observations: Presenting signs included fever, leg pain, and refusal to walk. Popliteal knee ultrasonography was unremarkable, whereas magnetic resonance imaging showed 2 intram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…According to Ngor et al [ 5 ], individuals with HIV infection were five times more likely to be diagnosed with pyomyositis than those uninfected. Meesiri [ 12 ] suggested an association between pyomyositis and systematic lupus erythematosus, while other authors suggested a correlation between hematological malignancies and pyomyositis [ 13 15 ]. Most patients show a full recovery with no long-term complications.…”
Section: Introductionmentioning
confidence: 99%
“…According to Ngor et al [ 5 ], individuals with HIV infection were five times more likely to be diagnosed with pyomyositis than those uninfected. Meesiri [ 12 ] suggested an association between pyomyositis and systematic lupus erythematosus, while other authors suggested a correlation between hematological malignancies and pyomyositis [ 13 15 ]. Most patients show a full recovery with no long-term complications.…”
Section: Introductionmentioning
confidence: 99%